Improving Financial Institution Pension Fund brand Awareness: Penetrate the Digital Native Generation Market to Increase Pension Fund Participation (A Case Study of DPLK PT PRQ) - Saraswati, Nadhira Diva (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This study explores how Instagram marketing strategies influence brand awareness for pension fund programs, with a particular focus on Generation Z (Gen Z). As digital natives, Gen Z exhibits distinct consumer behaviors that pension fund providers, like DPLK PT PRQ, need to understand and address to boost participation in pension plans. Although pension funds are crucial for financial stability, Gen Z's participation remains low, largely due to a lack of awareness and engagement. This research examines how Instagram, a platform favored by Gen Z, can be an effective channel for increasing brand awareness and encouraging greater involvement in pension programs. The study hypothesizes that Instagram usage positively affects brand awareness of DPLK PT PRQ's pension fund program, while also exploring the role of high-quality content in increasing both brand recognition and consumer trust. Additionally, it aims to assess the relationship between enhanced brand awareness and Gen Z’s willingness to participate in pension plans. A mixed-method approach is applied, incorporating both quantitative surveys and qualitative content analysis to capture insights from Gen Z respondents. The findings indicate that although brand awareness through Instagram can improve perceptions, the actual participation in pension funds remains low. This suggests that Gen Z, prioritizing immediate rewards and lifestyle-oriented goals, requires more than just awareness; it necessitates content that resonates with their current financial aspirations and lifestyle values. This study adds to our understanding of how digital platforms like Instagram can transform marketing strategies for financial institutions targeting younger audiences. The findings highlight the importance of a comprehensive approach to building brand awareness, one that combines high-quality content with interactive features to build trust and encourage participation. For DPLK PT PRQ, the research suggests enhancing content strategies by incorporating more interactive elements, such as polls, quizzes, and financial challenges, to foster greater engagement.